IMPACT OF SECTORAL GROWTH ON EMPLOYMENT ABSORPTION: EVIDENCE FROM KEY INDONESIAN INDUSTRIES - Awaludin, Azrul Afrillana; Al Khaidar, Moch Aridhi; Cholil, Muhammad; Rusgianto, Sulistya (Fakultas Ekonomi dan Bisnis, UNTAN, 2024)
This study aims to analyse the impact of growth in key industrial sectors on labor absorption in Indonesia, using time series data from 2011Q1 to 2023Q4 and employing the Autoregressive Distributed Lag (ARDL) model. This method captures the long-term and short-term relationships between industrial growth and labor absorption. The findings reveal that, in the long term, the oil and gas processing industry, non-oil and gas manufacturing, trade, and finance sectors significantly influence labor absorption. In contrast, the agriculture and mining sectors do not show a significant long-term effect. However, in the short term, all variables display varying impacts. Interestingly, the agriculture and mining sectors exhibit significant short-term effects despite their lack of long-term influence. This study contributes to the unemployment literature and suggests that the Indonesian government should focus on industrialisation to reduce unemployment. Industrialisation can stimulate job creation and support sustainable economic growth. These findings highlight the need for well-targeted policy strategies to optimise the industrial sector's role in reducing unemployment and enhancing economic stability.JEL: B22, E24, L60.